'The conflict is ours': community involvement in restorative justice. Issue 3 (2nd July 2016) - Gal, Tali
Abstract: Restorative justice (RJ) has attracted extended research relating to its potential to reduce crime, achieve fairness, and promote victims' well-being, but there is only limited discussion about the involvement of the community in RJ processes. This study employs grounded theory approach to analyze 26 documented files handled by a RJ program in Jerusalem, Israel. It proposes a multilayered construction of community involvement in RJ referring to four modes of community involvement: facilitators, community representatives, social networks, and the direct stakeholders. The analysis uncovers the unique characteristics of each entity, their potential contribution in promoting community interests, and the challenges in fulfilling their potential contribution. The Article further offers a responsive definition for community representation. Practical implications for RJ programs are discussed.